FEATURES OF INTERNATIONAL TRANSFER OF TECHNOLOGIES IN THE MODERN REALITIES OF MANAGEMENT SYSTEMS DEVELOPMENT - MANDYCH, Oleksandra; BABKO, Natalia; LYSHENKO, Margarita; KHARCHEVNIKOVA, Liliya (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the definition and analysis of the features of international technology transfer. The aggravation of the economic situation in Ukraine, first as a result of the Covid-19 pandemic, and later as a result of a full-scale invasion, significantly affected all socio-economic processes both within our country and on a global scale. The result of such modern challenges was a slowdown in global economic growth. In order to activate the innovative environment in Ukraine, it is necessary to solve the issue of ensuring the exit of domestic progressive technologies, including those produced by small and medium-sized enterprises, to world markets. Therefore, international transfer is the priority direction of Ukrainian innovation policy. Since the goal of technology transfer is precisely the economic growth and improvement of the population’s well-being, its development acquires urgent significance in terms of solving the problems outlined above. The article examines the essence and features of international technology transfer. The positive features of technology transfer are identified. The stages of technology transfer are characterized. In the conditions of recovery and development of the Ukrainian economy, the construction of an effective technology transfer mechanism will be based on the construction of an effective mechanism of interaction between the state and business structures, the development of technology transfer centers, and the expansion of state policy in the field of technology transfer. It has been determined that increasing the efficiency of the technology transfer mechanism will contribute to increasing the level of development of information and communication technologies through the creation of specialized scientific and technological platforms. Forms of technology transfer are outlined. Sources of technology transfer commercialization are considered. The main methods of commercialization of technology transfer are defined.